Ensemble modeling to predict the impact of future climate change on the global distribution of Olea europaea subsp. cuspidata - Khan, Sajid; Verma, Susheel (Frontiers in Forests and Global Change, 2022)
Climate change is one of the prime factors influencing global species redistribution. As a result, a better understanding of the species' possible range change in future climate conditions is needed. Here we compile global geographic occurrence data of a wild olive sub-species Olea europaea subsp. cuspidata and projected potential distribution models under current and future climate scenarios. Present study using ensemble modelling predicted that the species will undergo a significant decrease in habitat suitability under future climatic conditions with a contraction ranging from ca. 41% and 42% under RCP4.5 2050 and to about 56% and 61% under RCP8.5 2070 for committee averaging and weighted mean respectively. More specifically, there will be a decrease in habitat suitability in regions of Southeastern part of United States in North America; coastal regions in South America; coastal regions in the majority of eastern Africa; coastal parts of Spain, France, Italy, and Greece in Europe; coastal parts of Yemen and Saudi Arabia, the southeastern parts of Pakistan and southern part of China in Asia; southwestern and eastern parts of Australia when compared to current habitat suitability. The results of this ensemble modelling could be extremely valuable in identifying cultivation hotspots for effective restoration and protection of this olive lineage under future climatic conditions.